(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
B-cell precursor acute lymphoblastic leukemia (B-ALL) is the commonest cancer in children, comprising over 80% of the entire childhood leukemia. However, the etiology of childhood B-ALL remains poorly understood and genetic susceptibility is a major risk factor for this disease. ARID5B appeared as one of the most promising genetic markers with nearly a 3-fold increased risk of disease. Method: In this meta-analysis, a total of six candidate ARID5B polymorphisms (i.e. rs10821936, rs10994982, rs7089424, rs10821938, rs10740055, and rs7073837) which have been analyzed in at least 2 studies were included for analysis of the risk association between ARID5B polymorphisms and childhood B-ALL. Results: Pooled analysis revealed that the dominant model of these six ARID5B polymorphisms was associated with an increased risk of childhood B-ALL. However, subgroup analysis based on ethnicity suggested that only four polymorphisms (i.e. rs10821936, rs10994982, rs7089424 and rs10821938) consistently conferred increased risk to childhood B-ALL across different populations, whereas the other 2 polymorphisms (rs10740055, rs7073837) were causative to Caucasians (OR=2.01, 95% CI=1.66-2.44; OR= 1.98, 95% CI=1.69-2.31) but maybe protective for Asian (OR=0.49, 95% CI=0.22-1.09; OR=0.95, 95% CI=0.43-2.09) respectively. Conclusion: Our meta-analysis demonstrated could serve as promising markers for assessing the susceptibility risk to childhood B-ALL in both the Asian and Caucasian populations. Further development of a multigene panel inclusive of ARID5B is desirable for screening children with a higher risk of developing B-ALL and to improve clinical management of the disease.